Implementasi Metode Weighted Aggregated Sum Product Assessment (WASPAS) Pada Sistem Pendukung Keputusan Dalam Pemilihan Desa Terbaik Di Kecamatan Seginim - Yoselah Triani; Sapri Sapri; Reno Supardi (Jurnal Media Infotama, 2025)
Selection of the best village in Seginim District requires a systematic and objective approach to assess various influencing factors. One method that can be used to support decision making is the Weighted Aggregated Sum Product Assessment (WASPAS) method, which combines value-based assessment with criteria weighting. This study aims to implement the WASPAS method in a decision support system (DSS) in selecting the best village in Seginim District based on several predetermined criteria, such as level of development, infrastructure quality, health, education, and community economy. In its implementation, each village is evaluated by giving weight to each criterion according to the priorities that have been set, then the assessment results are combined to obtain a final value that indicates the village with the best performance. The results of this study are expected to provide effective and efficient solutions in the process of selecting the best village, as well as provide a strong basis for fairer and more transparent decision-making at the government level